Growth and Survival Parameters and Blood IgG and Total Protein Levels of Calves Born in the First Production Year of Brown Swiss and Simmental Cows - BAYKAN, Zeynep KÜÇÜK; ÖZCAN, Mustafa (Animal Review, 2017)
The objectives of this study were to determine the growth and survival parameters and blood IgG and total protein levels of calves born in the first production year of Brown Swiss and Simmental cows imported from Austria to a newly-established dairy cattle enterprise in Manisa, Turkey. The study material consisted of 62 Brown Swiss and 266 Simmental calves. Calves were separated from their mothers after birth and put into individual sections and subjected to colostrum feeding. At the end of three days, calf grower feed was given. Calves were weaned around 60-days of age unless there was an abnormality with their development. Birth weights, weaning weights on the 65th day, and daily weight gains of calves were 40.31 kg and 41.76 kg, 77.16 kg and 83.9 kg, 0.56 kg and 0.64 kg for Brown Swiss and Simmental breeds respectively. Simmental calves were born heavier and had more weight gain until weaning. We determined that breed and sex affected calves’ growth while delivery method only affected birth weight. Calves with high birth weights caused difficult birth, but this effect disappeared until weaning. Survival rates of calves until weaning were 98.39% for Brown Swiss and 95.49% for Simmental. The survival and mortality rates of Brown Swiss and Simmental calves at weaning were at normal levels, while the calves with difficult birth had losses around 10%.